Efektivitas On the Job Training Pada Kinerja Karyawan: Literature Review - Syam, Muhammad Luthfi Ichsan (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to examine the effectiveness of the On the Job Training (OJT) method in improving employee performance within organizational or corporate environments. The objective of this article is to assess the extent to which OJT contributes to performance enhancement. Through a literature review, this article analyzes the relationship between workplace-based training and performance improvement through several influencing factors. Methodology/approach: This research employs a Systematic Literature Review (SLR) approach based on 11 selected articles sourced from various national and international journals. Results/findings: The review findings indicate that OJT is an adaptive, applicable, and effective training method across various work sectors, including private industry, government institutions, and vocational education. Conclution: The findings indicate that OJT is an adaptive, applicable, and effective training method across various work sectors, including the private sector, government, and education. It can be concluded that OJT consistently contributes positively to the improvement of technical competencies, work efficiency, and employee adaptability in dynamic work environments. Limitations: This study is limited by its exclusive reliance on literature review without direct empirical data from the field. As such, the findings are conceptual and general in nature, and do not provide specific illustrations of OJT implementation within particular industries or organizational contexts. Further research using quantitative approaches or case studies is recommended to empirically validate these findings in practical settings. Contribution: This study contributes to the field of human resource management by highlighting the importance of On the Job Training as a strategy for enhancing employee performance.